Effect of black pepper (Piper nigrum) and cinnamon (Cinnamomum verum) on properties of reduced−fat milk−based ice cream - Samakradhamrongthai, Rajnibhas Sukeaw (Food and Applied Bioscience Journal, 2020)
The objective of this research was to study the effect of black pepper powder (BP) and cinnamon powder (CP) to be used as ingredients in reduced−fat milk−based ice cream. Total extractable phenolic content (TPC), 2,2−diphenyl−1−picrylhydrazyl (DPPH) radical scavenging, ferric ion reducing antioxidant power (FRAP) activity, and 2,2'−azino−bis (3−ethylbenzothiazoline−6−sulphonic acid) (ABTS) radical scavenging of BP and CP determined and expressed as mg of Trolox equivalent. In addition, the mixed spice (BP and CP) was mixed into reduced−fat ice cream and evaluated physical, chemical, and sensory properties. The results indicated that BP and CP exhibited a high value of TPC (656.91 ± 17.00 and 2391.85 ± 178.90) and showing the potential of antioxidant properties based on DPPH (18.54 ± 7.10 and 87.31 ± 1.50), FRAP (37.45 ± 3.10 and 108.09 ± 4.50), and ABTS (80.37 ± 19.70 and 701.49 ± 9.40), respectively. Moreover, the reduced−fat ice cream mixed with difference amount of mix spice exhibited the significance of physical and chemical properties. The reduced−fat ice cream with 0.1% mixed spice showed the suitable properties of viscosity (452.23 ± 5.10), melting rate (0.18 ± 0.01), overrun (43.46 ± 4.10), and hardness (7.72 ± 0.71). The sensory evaluation of the reduced−fat ice cream without mixed spice and 0.1% mixed spice also provided high sensory rating scores in the range of 6.5−7.7 and 6.3−6.8, respectively with higher TPC and antioxidant activities in the reduced−fat ice cream with 0.1% mixed spice. In conclusive, the BP and CP can be used as flavouring agent in reduced-fat dessert product and can be used as functional ingredients to create functional dessert.